Survival benefit associated with early detection of spontaneous bacterial peritonitis in veteran inpatients with cirrhotic ascites. Issue 3 (17th December 2019) - Townsend, Luke; Blais, Pierre; Huh, Alex; Nayak, Leela; Elwing, Jill E; Sayuk, Gregory S
Abstract : Background: Spontaneous bacterial peritonitis (SBP) is common in hospitalized cirrhotic patients with ascites and carries high mortality. This study aimed to determine whether early diagnostic paracentesis (EDP) <12 h of hospitalization conveys an intermediate‐term (6‐month) survival benefit in cirrhotic patients diagnosed with SBP. Methods: Consecutive US veterans with cirrhosis diagnosed with SBP over 13 years at a single VA medical center were reviewed retrospectively. Kaplan‐Meyer analyses assessed the effects of EDP on survival. Results: A total of 79 cirrhotic patients were diagnosed with SBP (61.8 ± 8.8 years, n = 77 male, n = 52 [66.8%] Caucasian, n = 23 [29.1%] African‐American). Underlying liver diseases included hepatitis c viral infection (HCV) (17.5%), alcohol (28.6%), alcohol and HCV (30.1%), and cryptogenic/metabolic (15.9%). Median baseline model for end‐stage liver disease (MELD) was 12 (range 6–34), and median MELD at presentation was 18. Seven subjects had a history of hepatocellular carcinoma (11.1%), and 26 (41.3%) presented with sepsis. Thirty‐three (52.4%) subjects died within 6 months after the SBP admission. Of the subjects, 41 (65.1%) underwent EDP, of which 23 (56.0%) survived at least 6 months, compared to only 7 of the 22 patients (31.8%) undergoing paracentesis >12 h from presentation ( P = 0.057). The maximal benefit of EDP on survival was observed beyond days 14 and 30; at these time points, no statistical difference in mortality was discernable ( P = 0.55 and 0.71). In a multivariate model including age, MELD at admission, hepatocellular cancer, and sepsis criteria, EDP (p 0.034) positively impacted patient survival at 6 months. Conclusions: EDP is associated with improved 6‐month mortality in cirrhotic patients with ascites. In this veteran cohort, EDP was as important as MELD as a predictor of intermediate‐term survival. Abstract : This study evaluated 79 US Veterans with cirrhosis complicated by spontaneous bacterial peritonitis to determine whether early diagnostic paracentesis (EDP) <12 h of hospitalization conveys an‐intermediate term (6 month) survival benefit. Kaplan‐Meyer analyses assessed the effects of EDP on survival. EDP is associated with improved 6‐month mortality in cirrhotics with ascites. In this veteran cohort, EDP was as important as model for end‐stage liver disease as a predictor of intermediate‐term survival.